Women in Ancient Egypt: determination of legal status and peculiarities of marriage and family relations - I. A. Lohvynenko; Ye. S. Lohvynenko (Law and Safety)
The main factors that influenced the formation of the worldview of the ancient Egyptian woman have been investigated. The influence of religion on her understanding of the family, her place and purpose in society has been shown. The main criteria of social differentiation of women have been identified. The primary sources, in particular legal monuments, on the basis of which the legal status of women in Ancient Egypt is shown, have been analysed. The features of marriage and family relations have been characterised. The research is based on the principle of historicism. Historical and comparative as well as historical and genetic methods were used to study the peculiarities of marriage and family relations, normative and comparative and hermeneutical methods were used when working with primary sources. The gender approach has led to a comprehensive study of religious, political, legal norms and social institutions, such as the family, family, culture, and more.